Supreme Court Legal Principle Controversy in Civil Lawsuits (Between Civil Rights and Reporting of Criminal Acts) - Matona, Marshanda Adella D. (Innovative: Journal Of Social Science Research, 2024)
Focusing on the execution of the Electronic Information and Transactions Law, this paper seeks to explore the legal conflict that arises from the restriction of civil lawsuits against criminal reporters in Indonesia. This contradiction arises from the fact that the civil rights of those who feel wronged by the report are disregarded, but the jurisprudence of the Supreme Court shields reporters from civil litigation in an effort to promote involvement in reporting illegal crimes. This study employs a juridical-analytical approach to normative legal research, which involves analyzing pertinent statutes and regulations, such as those pertaining to the Civil Code, the Electronic Information and Transactions Law, and the jurisprudence of the Supreme Court. Case studies illustrating the conflict between reporters' rights and the civil liberties of the reported are also included in this research. The study's findings highlight the need of respecting the civil rights of parties harmed by baseless reports, even as protecting reporters is crucial to preserving the honesty of the criminal justice system. Efforts must be made to bring these two legal interests into harmony by changing regulations and enforcing them more fairly. This will ensure that the rights of the reporter and the person who feels wronged are properly balanced.